2011
DOI: 10.1097/mpa.0b013e318214fe42
|View full text |Cite
|
Sign up to set email alerts
|

The Etiology of Acute Recurrent Pancreatitis in Children

Abstract: Recurrent pancreatitis in children has several etiologies. Genetic testing confirms the high frequency of CFTR mutations. This suggests that it is of some value to identify patients with late-onset CF and CFTR-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 40 publications
5
51
0
2
Order By: Relevance
“…Sánchez-Ramirez et al 18 observaram 36 crianças com diagnóstico de PA e 19 com pancreatite recorrente, concluindo que em cerca de 35% dos casos a causa era idiopática, mesmo após investigação completa, conforme já apontado em estudos anteriores, que descrevem valores entre 10-20% de PA idiopática em crianças 19,20 . Ainda, evidências recentes apontam que parte significativa dos casos de pancreatite idiopática em crianças está relacionada a mutações genéticas diversas 18,21 , responsáveis pela ocorrência da doença diretamente ou predisponentes desta, muitas das quais localizadas no braço longo do cromossomo 7 (7q35), onde muitos genes envolvidos com a transcrição e regulação do tripsinogênio estão localizados 22 .…”
Section: Pancreatite Aguda Recorrente Hereditária: Aspectos Genéticosunclassified
“…Sánchez-Ramirez et al 18 observaram 36 crianças com diagnóstico de PA e 19 com pancreatite recorrente, concluindo que em cerca de 35% dos casos a causa era idiopática, mesmo após investigação completa, conforme já apontado em estudos anteriores, que descrevem valores entre 10-20% de PA idiopática em crianças 19,20 . Ainda, evidências recentes apontam que parte significativa dos casos de pancreatite idiopática em crianças está relacionada a mutações genéticas diversas 18,21 , responsáveis pela ocorrência da doença diretamente ou predisponentes desta, muitas das quais localizadas no braço longo do cromossomo 7 (7q35), onde muitos genes envolvidos com a transcrição e regulação do tripsinogênio estão localizados 22 .…”
Section: Pancreatite Aguda Recorrente Hereditária: Aspectos Genéticosunclassified
“…In non-CF children, a single episode of acute pancreatitis can lead to insulin requiring diabetes mellitus (67). Pancreatic-sufficient CF patients are most susceptible to acute pancreatitis during adolescence and young adulthood (68)(69)(70), while pancreatic-insufficient patients rarely develop acute pancreatitis. Based on the CF ferret, inflammation association with the onset of exocrine pancreas decline appears closely linked to spontaneous glucose abnormalities and worsening of glucose tolerance.…”
Section: Methodsmentioning
confidence: 99%
“…Causes of recurrent pancreatitis in pediatrics are different than those in adults. While hereditary pancreatitis is one of the causes that should be excluded by genetic testing for (CFTR, PRSS1, and SPINK1 gene mutations) [5] and this was negative. Also the imaging studies showed no sign of pancreatic inflammation of duct injury in any of the imaging this patient had.…”
Section: Discussionmentioning
confidence: 99%
“…There is no history of abdominal trauma and his initial episode of pancreatitis was evaluated extensively and it was considered idiopathic. Since that time has had at least five known episodes of pancreatitis with mild elevation of his amylase and lipase (range: 200 -300), he had negative genetic testing for the hereditary pancreatitis common mutations (CFTR, PRSS1, and SPINK1 gene mutations) [5]. He was found to be heterozygous for HLA DQ2, but celiac serologies were negative.…”
Section: Case Reportmentioning
confidence: 99%